Taxonomy of the epistemological integration forms between disciplines: development of the “classical” theoretical tradition in Latin America: Taxonomy of the epistemological integration forms between disciplines: development of the “classical” theoretical tradition in Latin America - BERRIDY , Damián Ignacio; FERNÁNDEZ GUILLERMET, Armando (Utopía y Praxis Latinoamericana, 2021)
The paper presents a systematization of the contributions of several Latin American authors to the debate on the taxonomy of the forms of cooperation, coordination and integration between disciplines. To this end, we adopt a conceptual reference where the ideas of coexistence, combination and unification between disciplines are included in a continuum of increasing convergence. We consider that the scheme accounts for the European or “classical” tradition of thinking on inter-disciplinarity. On these bases, we develop a classification scheme that is compatible with the “classical” tradition, and with the categories that emerged from the work of the Latin American authors.